The garden as a metaphor for paradise - Adlard, Michelle Catherine (Rhodes University, Faculty of Humanities, Department of Fine Art, 2001)
In this half thesis the use of the garden as a metaphor for paradise has been explored. The English word " paradise" was derived from the Greek word " paradeisos" which in turn was derived from the Old Avestana " pairi-daeza," meaning an enclosure. In Ancient Persia the concept applied to an enclosed garden in the modern sense of the word. For this reason the thesis begins with an examination of the development of the garden in this desert region. A more-or-less continuous chain of development in both the physical and allegorical nature of the garden is traced through history from these Ancient Persian beginnings to the height of Mughal architecture (epitomised by the Taj Mahal), by way of the Muslim expansion through Central Asia and Europe. While the core elements of garden design were set in Ancient Persian times, and recur throughout the period studied, the impact of Islam on the local Persian culture brought about a new development of allegorical meaning associated with the garden. This allegorical development reached its apex, too, in the Taj Mahal in which, it is argued, the metaphorical representation of paradise in the garden tomb was made astonishingly explicit. The research for this mini thesis was gathered from secondary sources, including many published books and academic papers, photographic and diagrammatic evidence of extant ancient gardens, and reproductions of carpet designs.
Keywords: Paradise in art; Garden of paradise; Gardens -- Design -- Early works to 1800